Steady-State Heat Flux Prediction to Slabs in a Walking Beam Furnace. Issue 1 (15th December 2023) - Ahmed, Zaaquib Yunus; T'Jollyn, Ilya; Lecompte, Steven; Demeester, Toon; De Raad, Teun; De Paepe, Michel
Abstract: After casting steel slabs are reheated in a reheat furnace to temperatures in the range 1200-1250 °C in order to be suitable for rolling. The high energy requirements and the importance of reheating for quality control are the motivation behind numerically modeling the furnace. Computational fluid dynamics allows us to understand the fundamental physics with great detail. It is however unclear how assumptions of such models influence the results of the simulations. In this work a steady-state model was analyzed, and it was found that the chosen slab temperature profile can underestimate the average heat flux on the slab surface by 30%. A slab model was employed to simulate the transient slab temperatures which results in an underestimation of the average slab temperatures by about 500 °C for the case with reduced fluxes. The uniform slab temperature assumption also results in the overestimation of heat fluxes on its front and side face.